2015
DOI: 10.1017/s1759078715000239
|View full text |Cite
|
Sign up to set email alerts
|

Distance measurements and limitations based on guided wave 24 GHz dual tone Six-port radar

Abstract: In the following, a continuous wave radar system based on the Six-port principle will be shown for measurement tasks at enclosed systems needing micrometer accuracy as well as high update rates like tank level monitoring or hydraulic cylinder piston control. To exceed the ambiguity limit of such an interferometric system, a dual tone approach is used. The system will be presented with measurement results at 24 GHz within a WR42 waveguide to prove the feasibility of the proposed concept. Furthermore, considerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In comparison with Interferometer radar [6], AMCW radar has considerably larger ambiguity-free detection window. Dual tone Interferometer or 2-FSK radar can be used for enlarge ambiguity-free window [7], however, tones are transmitted at different time slots therefore limits the refresh rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison with Interferometer radar [6], AMCW radar has considerably larger ambiguity-free detection window. Dual tone Interferometer or 2-FSK radar can be used for enlarge ambiguity-free window [7], however, tones are transmitted at different time slots therefore limits the refresh rate.…”
Section: Discussionmentioning
confidence: 99%
“…Interferometric radar [7] is using only one continues-wave (CW) signal, however, its ranging window equivalents to only one wavelength. In this paper, a millimeter wave amplitude modulated continuous-wave (AMCW) radar is proposed, which occupies little bandwidth, yet can measure distance to target with micrometer accuracy with a ranging window of 15 cm.…”
Section: Introduction Industry 40 Was Initially Proposed By the Gmentioning
confidence: 99%
“…It is obvious from the periodicity of the beat signal that the unambiguous range is extended from about 6 mm for the single tone evaluation of f1 or f2 up to 60 mm. This range extension depends on the selected frequency spacing and is limited to a few meters, which is discussed in [68]. …”
Section: Discussionmentioning
confidence: 99%
“…However, this also means a varying transmit frequency, thus a poor phase noise and a large standard deviation of the range measurement. For unmodulated CW radars, this effect was described analytically by [26], [27]. Moreover, it was shown that a close target leads to a strong correlation of sent and received phase noise due to the short propagation time, causing a smaller root mean square (RMS) distance error.…”
Section: B Signal Generationmentioning
confidence: 99%
“…Examples are the measurement of levels of fluids and solids in storage tanks [2]- [4], where a radar sensor is preferred over conventional systems to avoid direct contact to the sample. Especially if oil or gas at a high pressure is used, for example to displace pistons or hydraulic cylinders, radar systems are an attractive alternative [5]- [7].…”
Section: Introductionmentioning
confidence: 99%